Parents’ understanding and attitudes toward the application of AI in pediatric healthcare: a cross-sectional survey study - Huang, Yan-Dan; Zeng, Shu-Long; Lin, Jie; Mao, Zhi-Peng; Zhang, Qi-Liang; Feng, Gao-Zhong; Ou, Qiong-Xia (Frontiers in Public Health, 2025)
ObjectiveTo investigate parents’ understanding and attitudes toward the application of Artificial Intelligence (AI) in pediatric healthcare.MethodsAn observational, cross-sectional study was conducted using an ad hoc questionnaire. Between February and April 2025, 200 family members of children receiving care at our hospital voluntarily participated in the study. Inclusion criteria included being a family member of a child treated at the hospital. Exclusion criteria were an inability to understand the questionnaire and incomplete responses. The AI applications referenced by respondents primarily included large language models such as ChatGPT, DeepSeek, and Kimi, among others. The questionnaire consisted of two sections: demographic information, and attitudes toward the use of AI in pediatric healthcare. Data were analyzed using SPSS (version 25.0). Quantitative variables were expressed as mean and standard deviation, and categorical variables using frequencies and percentages. Group comparisons were performed using chi-square test and t-test (p-value < 0.05).ResultsA total of 185 participants completed the questionnaire. Participants who were unaware of AI applications in pediatric healthcare were more likely to be older, have lower educational levels, and reside in rural areas. The majority of respondents (71.2%) believed that the information provided by AI was partially accurate, while 6.9% considered it partially inaccurate. Regarding perceived benefits, 74% identified convenience as the main advantage of AI in pediatric care, followed by 41.1% who cited high diagnostic efficiency. Key concerns included perceived inaccuracy and the potential for misdiagnosis (52%), as well as uncertainty regarding accountability in the event of an error (44.5%). Most participants (91.1%) believed that AI cannot replace doctors in the future.ConclusionAlthough most parents were aware of the use of AI in pediatric healthcare and recognized its convenience and efficiency, they expressed concerns about accuracy, accountability, and data privacy. A notable lack of awareness was observed among older individuals, those with lower levels of education, and residents of rural areas.